Hubungan Safety Leadership dengan Safety Performance Pada Pekerja Industri Pakan Ternak Sidoarjo - Agustina, Agustina; Chahyadhi, Bachtiar; Ardyanto, Denny (Preventia: The Indonesian Journal of Public Health, 2019)
The direct cause of accidents often involves human error, organizational factors and management are involved in incidents in all industries. An old paradigm of domino theory which emphasizes that accidents always stem from management mistakes start slowly changed. Human factors such as behavior, motivation, psychology began to be considered. False a behavioral approach to implement a safety culture with safety leadership.This study aims to analyze the relationship between safety leadership factors with safety performance in animal feed industry workers in Sidoarjo. This research is a quantitative study with a cross-sectional approach. The method used to measure the safety leadership factor with safety performance is by filling out questionnaires.The population in this study were 150 people and samples were obtained using the techniquesimple random sampling of 108 workers. The results showed that there wasa correlation between the roleof safety leadership of supervisors and safety performance of 0.023.Suggestions that can be applied to improve safety performance with add jobdesk safety leadership to supervisors to motivate and direct workers to participate in company safety programs and by promoting workers who have a leadership style of achievement orientation become a supervisor.